Corona Virus (Covid-19) in Nigeria: Philosophical Reflections - Nwaokugha, Douglas O. (NIU Journal of Social Sciences, 2021)
Corona virus (covid-19) as a novel health challenge has paralyzed and wrecked havoc on social, economic and political activities of states. On its outbreak, most states could not put up effective fight due to infrastructural and personnel deficits, a revelation that most states had lost the fight against covid-19 before its arrival in their states. Using the philosophical approach, this paper philosophically discusses covid-19 with emphasis on how its challenges can become a springboard that can trigger opportunities in states for addressing their monumental infrastructural and personnel deficits. Addressing states’ monumental infrastructural and personnel deficits can be sure bets for the sustainable development of states. The paper suggests that states should develop plans for providing their citizens adjustment mechanisms to the pandemic as well as effectively collaborate with scientists, technologists, universities and research institutes for solutions as against the current practice of total lockdown of the economy, private and public institutions without practical solutions on how to address the challenges of the pandemic. Keywords: covid-19, pandemic, Nigeria, philosophical reflections.